The Rice of Online Learning During the COVID-19 Pandemic in Sri Lanka - Wanigasingha, C.B. (SDU of the Faculty of Social Sciences, Faculty of Social Sciences, University of Kelaniya, Sri Lanka, 2020)
Educational institutions (schools, colleges, and universities) in Sri Lanka are currently based on traditional methods of learning, that is, we follow the traditional set up of face-to-face lectures in a classroom. Although many academic units have also started blended learning, still a lot of them are stuck with old procedures. The sudden outbreak of a deadly disease called Covid-19 caused by a Corona Virus (SARS-CoV-2) shook the entire world. The World Health Organization declared it as a pandemic. This situation challenged the education system across the world and forced educators to shift to an online mode of teaching overnight. Many academic institutions that were earlier reluctant to change their traditional pedagogical approach had no option but to shift entirely to online teaching–learning. The article includes the rice of online learning, importance of online learning and Strengths, Weaknesses, Opportunities, & Challenges analysis of e-learning modes in the time of crisis.
Keywords: Covid - 19, Education, Online Learning, Technology